1996
DOI: 10.1080/07391102.1996.10508105
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Labeled Nucleotide Mobility in the Boundary of theEcoRI Endonuclease Binding Site

Abstract: A complex consisting of the EcoRI endonuclease site-specifically bound to spin-labeled DNA 26mers was prepared to provide a model system for studying possible conformational changes resulting from protein binding. EPR was used to monitor the mobility of the spin labels that were strategically placed in position 6, 9, or 11 with respect to the dyad axis of the 26mer. These positions are located within the flanking region on either side of the EcoRI hexamer binding site. This allows the monitoring of potential d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Results similar to those obtained in this study have been observed in earlier investigations wherein spin-labeled nucleic acid molecules were used to study the structure of nucleoprotein complexes (8,9,39). While studying by EPR spectroscopy the encapsidation of spin-labeled poly(A) by tobacco mosaic virus (TMV) protein to form viral-like particles, a pronounced broadening of the EPR spectra was observed during in vitro assembly of the viral-like particle (8).…”
Section: Rna-protein Interactions Insupporting
confidence: 85%
See 1 more Smart Citation
“…Results similar to those obtained in this study have been observed in earlier investigations wherein spin-labeled nucleic acid molecules were used to study the structure of nucleoprotein complexes (8,9,39). While studying by EPR spectroscopy the encapsidation of spin-labeled poly(A) by tobacco mosaic virus (TMV) protein to form viral-like particles, a pronounced broadening of the EPR spectra was observed during in vitro assembly of the viral-like particle (8).…”
Section: Rna-protein Interactions Insupporting
confidence: 85%
“…Another study examining the binding of bacteriophage fd gene 5 protein to spin-labeled polynucleotides revealed a significant change in the EPR line shape upon formation of the DNA-protein complex (9). Finally, a complex of EcoRI bound to spin-labeled DNA oligonucleotides (containing the recognition site for EcoRI) was investigated by EPR spectroscopy to determine the conformational changes in the DNA that occur upon binding to EcoRI (39). The changes in spectral line shapes were used to infer that a spin label positioned proximal to the GAATTC recognition site is indeed influenced by the binding event (39).…”
Section: Rna-protein Interactions Inmentioning
confidence: 99%
“…In the case of proteins, molecules, and in order to apply this method to predict thiol-reactive nitroxide spin labels have been introduced the folding pathways of larger RNA molecules, six difmainly to cysteine-substituted sites [2][3][4][5]. For RNA oliferent short 10-mer RNA duplexes have been designed gonucleotides, spin labels can be covalently attached with spin labels attached at varying 2Ј positions (Figeither to modified bases [6][7][8] or the phosphate moiety ure 1) such that the interspin distances vary between [9, 10], or to the 2Ј position of the ribose ring [11,12].…”
Section: Sdsl Introduces Spin-label Molecules Into Desiredmentioning
confidence: 99%
“…The first line of work in-volves monitoring the dynamics of protein-nucleic acid complexes. This is accomplished by placing spin labels either inside the protein binding site, as with polylysine (Bobst et al, 1985) and gene 5 single-strand binding protein , or outside the binding site, as in the cases of the site-specific EcoRl endonuclease (Keyes et al, 1996) and the homeodomain (Bobst et al, 1996b). By placing the labels at various distances from the binding site, the transmission of structural information can be monitored.…”
Section: Introductionmentioning
confidence: 99%